Physiological Processes Underlying Short Interval Intracortical Facilitation in the Human Motor Cortex - Van den Bos, Mehdi A. J.; Menon, Parvathi; Howells, James; Geevasinga, Nimeshan; Kiernan, Matthew C.; Vucic, Steve (Frontiers in Neuroscience, 2018)
Short interval intracortical facilitation (SICF) may be elicited by a paired pulse transcranial magnetic stimulation (TMS) paradigm, whereby a suprathreshold first stimulus (S1) precedes a perithreshold second stimulus (S2). Other facilitatory circuits can be probed by TMS such as intracranial facilitation, however the cortical contributions to these circuits may lie partially outside of M1. SICF as such represents a unique analogue to M1 inhibitory circuits such as short interveal intracortical circuits. The aim of the present study was to provide insight into the physiological processes underlying the development of SICF using the threshold tracking TMS technique which was recently demonstrated to have significant reliability. TMS studies were undertaken on 35 healthy controls, using either a 90 mm circular and 70 mm figure of eight coil, and one of two targets (0.2 mV and 1.0 mV) tracked. The motor evoked potential (MEP) responses were recorded from the abductor pollicis brevis. SICF was consistently evident between interstimulus intervals (ISI) of 1-to-5 ms (P<0.001), with two peaks occurring ISIs 1.5 and 3 ms when using the circular coil. A significant SICF reduction (F=5.631, P< 0.05) was evident with the higher tracking target, while SICF increased when stimulating with the figure of eight coil. While there was correlation between SICF and CSP duration, there was no relationship between SICF and SICI or ICF. Age appeared to have no influence on SICF, SICI or ICF. Findings from the present work suggest that SICF appears to be mediated by I-wave facilitation.